2013
DOI: 10.1371/journal.pone.0079048
|View full text |Cite
|
Sign up to set email alerts
|

Prp22 and Spliceosome Components Regulate Chromatin Dynamics in Germ-Line Polyploid Cells

Abstract: During Drosophila oogenesis, the endopolyploid nuclei of germ-line nurse cells undergo a dramatic shift in morphology as oogenesis progresses; the easily-visible chromosomes are initially polytenic during the early stages of oogenesis before they transiently condense into a distinct ‘5-blob’ configuration, with subsequent dispersal into a diffuse state. Mutations in many genes, with diverse cellular functions, can affect the ability of nurse cells to fully decondense their chromatin, resulting in a ‘5-blob arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…However, there were only 5 targets in L0 vs L13, the 5 targets disappeared and the other 5 targets (prp22, hnRNPs, prp43, SF3b, Lsm) remained, indicated that the 5 targets were involved in the chilling and 0 °C treated responses. The 5 targets were responsible for mRNA splicing and alternative splicing, such as prp22 and splicesome components regulate chromatin dynamics [ 100 ]; the ATPase activity of prp43 was required for early steps of pre-rRNA processing and normal accumulation of mature rRNAs [ 101 ]; SF3B1 as a principal player in the spliceosome and as a target of inhibitor compounds in pre-mRNA splicing complex [ 102 ]; hnRNPs are complexes of RNA and protein present in the cell nucleus during gene transcription and subsequent post-transcriptional modification of the newly synthesized RNA (pre-mRNA), and the proteins involved in the hnRNP complexes were collectively known as heterogeneous rib nucleoproteins, which was regulated by phosphorylation catalyzed by protein kinase A and was responsible for suppressing RNA splicing at a particular exon by blocking access of the spliceosome to the polypyrimidine tract [ 103 ]. Lsm plays a large number of various roles in mRNA processing and regulation, and depending on which lsm proteins and RNA molecule were involved, this ribonucleic protein complex facilitated a wide variety of RNA processing including degradation, editing, splicing, and regulation [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, there were only 5 targets in L0 vs L13, the 5 targets disappeared and the other 5 targets (prp22, hnRNPs, prp43, SF3b, Lsm) remained, indicated that the 5 targets were involved in the chilling and 0 °C treated responses. The 5 targets were responsible for mRNA splicing and alternative splicing, such as prp22 and splicesome components regulate chromatin dynamics [ 100 ]; the ATPase activity of prp43 was required for early steps of pre-rRNA processing and normal accumulation of mature rRNAs [ 101 ]; SF3B1 as a principal player in the spliceosome and as a target of inhibitor compounds in pre-mRNA splicing complex [ 102 ]; hnRNPs are complexes of RNA and protein present in the cell nucleus during gene transcription and subsequent post-transcriptional modification of the newly synthesized RNA (pre-mRNA), and the proteins involved in the hnRNP complexes were collectively known as heterogeneous rib nucleoproteins, which was regulated by phosphorylation catalyzed by protein kinase A and was responsible for suppressing RNA splicing at a particular exon by blocking access of the spliceosome to the polypyrimidine tract [ 103 ]. Lsm plays a large number of various roles in mRNA processing and regulation, and depending on which lsm proteins and RNA molecule were involved, this ribonucleic protein complex facilitated a wide variety of RNA processing including degradation, editing, splicing, and regulation [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prolonged development of defective egg chambers is eliminated by mid-oogenesis arrest resulting in egg chamber degeneration around stages 9 to 10 ( Baxley et al, 2011;Harrison et al, 1993;Klug et al, 1968). This defective chromatin dispersal is a common trait among a large number of unrelated mutants, such as genes encoding the splicesosome component prp22 (Klusza et al, 2013), the piwi-interacting RNAs (piRNAs) related protein, and rhino (Klattenhoff et al, 2009;Volpe et al, 2001), which complicates the identification of the mechanisms associated with Su(Hw) activity in the genome of egg chamber cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all ovarioles of hemk2 -GLKD harbored nurse cell nuclei containing chromosomes remained in a blob-like configuration even beyond stage 6 (Figure 2B, Figure S2A; 99%). In order to investigate the possible causes that may results in this chromosomal defect, we examined the expression level of the genes which were known to function for chromosomal dispersion (Goodrich et al, 2004; Klusza et al, 2013). Among those genes, qRT-PCR analysis revealed that the mRNA level of otu was most drastically reduced upon hemk2 -GLKD (Figure 2C), suggesting a potential correlation between otu expression and the observed defect.…”
Section: Resultsmentioning
confidence: 99%
“…S2A; 99%). To investigate the possible causes of this chromosomal defect, we examined the expression levels of genes known to be involved in chromosomal dispersion (Goodrich et al, 2004; Klusza et al, 2013). qRT-PCR analysis showed that the mRNA level of otu was significantly reduced in hemK2 -GLKD ovaries (Fig.…”
Section: Resultsmentioning
confidence: 99%